#TITLE_ALTERNATIVE# - ARIEF YAHYA (NIM 10202032), ADITYA
In nuclear reactions, probability of reaction occurrence is defined by a physical quantity named cross section. Calculation of cross section can be done either by experimental methods or computer simulation. In this research, calculation of cross section of neutron reaction with uranium isotopes from U-232 to/with U-241 using TALYS computer program has been done. TALYS results are total, elastic, non-elastic, and fission cross section, and then be compared with experimental data that provided in ENDF/B-VII which is released in 2006. TALYS is nuclear reaction simulation program which developed by A.J. Koning and M.C. Duijvestijn (NRG-Petten, The Netherlands) and S. Hilaire (CEA-Bruyeres-le-Chatel, France). Nowadays, newest version of TALYS is TALYS-1.0 which is released in 2007. TALYS is capable to simulate nuclear reactions that involve neutrons, gamma-rays, protons, deuterons, helions, and alpha-particles, in 1 keV-200 MeV energy range.